2021
DOI: 10.21203/rs.3.rs-514820/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidimensional Geriatric Evaluation in Acromegaly: A Comparative Cross-Sectional Study

Abstract: Background: Improvement in acromegaly management increased disease survival and prevalence. Evidence regarding acromegaly in older adults are sparse. We aim to explore acromegaly impact on aging process quality.Methods: Multicenter case-control study conducted on 42 older adults (≥ 65 years) acromegaly patients (ACRO) compared to an age- and gender-matched control group (CTR). Each participant underwent a multidimensional geriatric evaluation.Results: Mean age in both groups was 73 ± 6 years and female gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These data suggest that also the physiological process of aging may play a crucial role in the occurrence of VFs in older patients with acromegaly [42]. Moreover, in a recent case-control study, acromegaly patients aged over 65 years old showed more frequently musculoskeletal and bone diseases than no-acromegaly matched group (52% vs. 12%; 64% vs. 10%; P < 0.05) supporting that aging and acromegaly could affect both negatively bone health [43]. Osteoporosis is considered the most common metabolic disease in the elders with a prevalence of around 39% in study population in elders in 2020 in Spain and China [44].…”
Section: Discussionmentioning
confidence: 69%
“…These data suggest that also the physiological process of aging may play a crucial role in the occurrence of VFs in older patients with acromegaly [42]. Moreover, in a recent case-control study, acromegaly patients aged over 65 years old showed more frequently musculoskeletal and bone diseases than no-acromegaly matched group (52% vs. 12%; 64% vs. 10%; P < 0.05) supporting that aging and acromegaly could affect both negatively bone health [43]. Osteoporosis is considered the most common metabolic disease in the elders with a prevalence of around 39% in study population in elders in 2020 in Spain and China [44].…”
Section: Discussionmentioning
confidence: 69%